Preparation of Some 1,2,4-Triazol Schiff Bases as Urease Inhibitors and Study Their Effect on Proteus Mirabilis Bacteria - Turky, Zahraa A; Ahmed, Salman A (Al-Nahrain Journal of Science, 2018)
The basic nucleus 4-(amino)-5-phenyl-l-4H-1,2,4-triazole-3-thiol was prepared by cyclisation of potassium dithiocarbazinate with hydrazine hydrate using ethanol as solvent under reflux condition for 3-4 hrs.. The compound which has been synthesized successfully was subjected to addition reaction with different aldehydes to synthesize Schiff bases. The compounds were confirmed by[ physical parameters (solubility, melting point),1H nuclear magnetic resonance (1HNMR)and spectroscopic methods (FTIR)]. All the synthesized compounds were screened for their urease inhibition. Some compounds showed excellent urease inhibition activity.